2018
DOI: 10.31296/aop.v2i6.73
|View full text |Cite
|
Sign up to set email alerts
|

Mental Disorders and Female Infertility

Abstract: Approximately 5 to 10 % of women in their reproductive years are affected by infertility. Infertility in women has been associated with depression, bipolar disorder, anxiety, disturbed eating behavior, autism, psychotic disorders and autism. Part of the association between depression, anxiety and infertility can be explained by the emotional stress resulting from infertility. As mental disorders like depressive disorder or eating disorders are also prospectively associated with infertility, a bidirectional rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Infertility diagnosis and the subsequent treatment process usually impose excruciating stress on couples. Several studies have reported that couples with infertility are prone to experiencing depression (6), anxiety (7), sexual intercourse problems, marital problem (8,9), decrease in selfconfidence (10), and low levels of psychological well-being (11,12) and quality of life (13).…”
Section: Introductionmentioning
confidence: 99%
“…Infertility diagnosis and the subsequent treatment process usually impose excruciating stress on couples. Several studies have reported that couples with infertility are prone to experiencing depression (6), anxiety (7), sexual intercourse problems, marital problem (8,9), decrease in selfconfidence (10), and low levels of psychological well-being (11,12) and quality of life (13).…”
Section: Introductionmentioning
confidence: 99%
“…In the world, ;5-10% of women at the reproductive age face some kind of infertility problem. Ovarian disorders are responsible for more than half of female infertility (1,2). Ovarian disorders include major reproductive diseases in human such as polycystic ovary syndrome (3) and ovulation with luteal insufficiency (4).…”
mentioning
confidence: 99%
“…7 Depression in women with infertility may affect treatment seeking, compliance to follow-up as well as hope for the future. 8 A review of the research literature from Pakistan shows that Shoaib et al (2004) looked at the mental health of females with infertility and found psychiatric morbidity in 76% of their study sample of which depression was the most common diagnosis (46.03%). 9 A similar study conducted by Verma India found 56.4% (79/140) of the infertile females to be suffering from depression.…”
Section: Introductionmentioning
confidence: 99%